Antioxidative Effects of Standardized Aronia melanocarpa Extract on Reproductive and Metabolic Disturbances in a Rat Model of Polycystic Ovary Syndrome - Jovan Rudic; Vladimir Jakovljevic; Nikola Jovic; Maja Nikolic; Jasmina Sretenovic; Slobodanka Mitrovic; Sergey Bolevich; Stefani Bolevich; Miroslav Mitrovic; Sasa Raicevic; Kristina Andric; Andjela Dimkic Milenkovic; et al. (MDPI AG, 2022)
Polycystic ovary syndrome (PCOS) represents the most common endocrinopathy among childbearing-age women, with oxidative stress (OS) underlying its etiopathogenesis. Metformin (MET) represents a frequently used agent in PCOS. However, weak results encourage alternative treatments. We aimed to investigate isolated and synergistic effects of Standardized Aronia melanocarpa extract (SEA) and MET for alleviating reproductive and metabolic PCOS abnormalities. PCOS induction was followed by 28-day treatment with MET, SAE, or MET + SEA. Bodyweight (BW), cyclicity, histological, and ultrasonographical ovarian analyses were performed. Hormonal, glycemic, and lipid profiles were accessed, as well as systemic and ovarian oxidative status; BW, cyclicity, ovarian histomorphology, ovarian volume, testosterone and progesterone levels, as well as LDL, triglycerides, and total cholesterol levels were aggravated after PCOS-induction and improved after MET, SEA, and MET + SEA treatment. MET + SEA had the greatest impact on glycoregulation. Alterations in OS parameters (TBARS, O2−, H2O2, catalase, superoxide dismutase, and reduced glutathione) could be responsible for observed differences; (4) Conclusions: Our findings confirmed that SAE alone or along with MET was capable of ameliorating reproductive and metabolic disturbances in the PCOS rat model, with the restoration of OS parameters. SAE alone did not alter the protective effects of MET in PCOS.